A Study of Various Technologies being used by Public and Private sector Banks: Exploring the link between bank service quality and customer satisfaction in Indian banks (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The study's major aim is to establish a link between bank service quality and customersatisfaction in both public and private banks. In recent years, Indian banks have seen significanttransformations from conventional banking to customer-centric convenience banking. The use of CoreBanking Solutions allows banks to improve consumer convenience by providing 'anywhere' and 'anytime'banking to guarantee that clients are comfortable. Indian banks have used IT-enabled and procedures toincrease revenue, improve customer satisfaction, and manage corporate risks while reducing costs.Age-Specific Analysis of Responsiveness, Age-Specific Analysis of Tangible